Cash economy: Tax evasion amongst SMEs in Malaysia - Mohamad, Azhar (2017)
Tax evasion is a punishable financial crime which is particularly rampant in underground cash economies. In this study, using proprietary tax audit data from the Inland Revenue Board of Malaysia on the 2011 tax returns of SMEs, we examine the relationship between tax evasion and certain demographic factors such as location, (engagement of) tax agent, size and type of SME’s industry. We find that tax evasion among SMEs in Malaysia is the highest when the business is located in a suburban environment and has no tax agent. Tax evasion is also influenced by the size of the SME (micro or medium). This study gives insight that the Inland Revenue Board of Malaysia can use to aid its collection department in profiling SMEs that have a higher tendency to evade paying tax.